Paul's Anthropology in Context: The Image of God, Assimilation to God, and Tripartite Man in Ancient Judaism, Ancient Philosophy and Early Christianity - Kooten, Geurt Hendrik van (Mohr Siebeck, 2023)
George H. van Kooten offers a radical contextualization of Paul's view of man within the Graeco-Roman discourse of his day. On the one hand, important anthropological terminology such as "image of God" and "spirit" derives from the Jewish creation accounts of Genesis 1-2. On the other hand, this terminology appears to be compatible with reflections of Graeco-Roman philosophers on man as the image of God and on man's mind, and is supplemented with Platonic concepts such as "the inner man." For this reason, the author traces the development of Paul's anthropology against the background of both ancient Judaism and ancient philosophy. Although he takes his starting point from Jewish texts, and is not out of tune with particular Jewish thoughts about the close relation between man and God, Paul, like Philo of Alexandria, seems to owe a lot to contemporary philosophical anthropology. Paul's view, for instance, that man needs to be "transformed into the image of God" lacks Jewish antecedents, but reflects the pagan philosophical notion of man's assimilation to God. George H. van Kooten emphasizes that it is no longer possible to deny the relevance of a Greek context for Paul's view of man, and argues that Paul should be understood in the wake of the 1st cent. BC introduction of a comprehensive Platonic doctrine of man's assimilation to God through virtue. Paul's anthropology, which calls for inner transformation and is universally applicable, criticizes the superficial values of the sophistic movement in Corinth and the anthropomorphic images of the gods, and offers a strategy to overcome the ethnic tensions which divide the Christian community in Rome